Peripheral neuropathy in angioimmunoblastic lymphadenopathy with dysproteinaemia. - Tredici, G (1979)
A case of angioimmunoblastic lymphadenopathy with dysproteinaemia complicated by a subacute peripheral neuropathy is described. Clinically the neuropathy was mainly motor, but pain and paraesthesiae in the legs were also present. Sural nerve biopsy indicated decreased numbers of myelinated fibres, mainly the largest, without actual signs of degeneration or regeneration. However, the occurrence of denervation bands indicated that degeneration had led to loss of myelinated fibres.